If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -3 = 9x + 5x Combine like terms: 3 + -3 = 0 0 = 9x + 5x Combine like terms: 9x + 5x = 14x 0 = 14x Solving 0 = 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 0 + -14x = 14x + -14x Remove the zero: -14x = 14x + -14x Combine like terms: 14x + -14x = 0 -14x = 0 Divide each side by '-14'. x = 0 Simplifying x = 0
| 13-30/x=x | | 8x-6y=36 | | m+m+2m= | | -2=6-z-z | | 4=4-6n-3n | | 15X^2+14X=27X | | 19-a+4a=7 | | (2n+2)(6n+1)=0 | | -6=12-4/8t | | 3(2)(4)-12/6(3)= | | (-3)(-5m)= | | 3(2)(4)-12*6= | | 3(2)(4)-12= | | 3x+2(-3+11)=7 | | 7-g=11 | | 12v-12v= | | ln(3x+1)=3 | | 8-40x=15x-40 | | 0.2(x+12)=12 | | 2k-4=6k-6 | | 5/8(n-2)=20 | | 1/5-x=3x/8-1 | | X^2-16x+64=128 | | .5(10)x=20 | | .5(10x)=20 | | t/-5-15=30 | | 9x-32=7x+4 | | h^2-h-22=0 | | -10+9v+v+7= | | 1/6(a-3)=10 | | 164=2(5x) | | -3+2g=55 |